Politics otherwise : Shakespeare as social and political critique - Donskis, Leonidas.; Mininger, J. D. (Value Inquiry Book Series, 2012)
The book is comprised of essays that utilize Shakespeare as a productive window into topics of contemporary social and political relevance. Its interdisciplinary qualities make the book relevant for students of political studies, literature, philosophy, cultural studies, and history.